(untitled) (Revista Internacional de Folkcomunicação, 2018)
This paper presents new and revisited ideas by cognitive memory from the re-reading and re-writing of my studies of the Folkcommunication theory developed by Luiz Beltrão. As communicational researchers we are advancing, but still little, we need to stimulate future generations. They will surely construct the building of a field of knowledge that has a Brazilian identity, without losing their universal vocation and without renouncing local commitment, converting each citizen into a custodian of the utopias that have been cradled in previous generations. Although repetitive as an author, always gathering and rewriting my Folkcommunication essays, I seek to encourage the more experienced as well as the new academics to the importance of pedagogical action, both in the university and in the corporate space. The literary course of this essay in its first part revisits the historical roots of the cultural archipelago highlighting the challenge of the interdisciplinary national dialogue in front of our continental nature. After the contextualization, I write Luiz Beltrão’s profile, as a journalist, teacher, researcher, academic and literary author. In presenting Folkcommunication as an academic discipline, situated on the frontier between Folklore and Communication, from the perspective of the symbolic agents’ collective influence in the context of peripheral communities, I warn the reader/researcher about the need to study critically, in the contemporarity, the roots of discipline and to map the boundaries, as well as inventory the subjects, objects and scenarios that border the Folkcomunicacional space. Finally, I express my thankful to the FOLKCOM’s members for their achieved maturity, visible in the flood of records on the theoretical or empirical incursions, and I invite all of you to continue on this Beltranian Journey. Luiz Beltrão Centenary; José Marques de Melo; Folkcommunication.